L. Wittgenstein on Ethics, Aesthetics and God: From Early Notebooks - Noreikienė, Jurgita (Problemos, 2000)
The discovery of Wittgenstein’s Notebooks 1914-1916 stimulated critical revision of traditionally established positivistic interpretation of Tractatus Logico-Philosophicus, and opened new possibilities for interpreting of this work. With regard to Notebooks it is possible to understand passages of the Tractatus which seem to be obscure and incomprehensible because of their laconic style. Especially it concerns Wittgenstein’s ethics, aestethics, and the concept of God. Notebooks permit much more exhaustive explanation of these topics and deeper understanding of Tractatus Logico-Philosophicus.